2017
DOI: 10.1111/jgs.14738
|View full text |Cite
|
Sign up to set email alerts
|

Life‐Space Mobility Change Predicts 6‐Month Mortality

Abstract: Background / Objective Limited mobility in the community, measured by life-space, is associated with long-term mortality; but little is known about changes in life-space over time predicting short-term mortality. We examined 6-month change in life-space mobility as a predictor of subsequent 6-month mortality for community-dwelling older adults. Design Prospective cohort study. Setting Community-dwelling older adults from five Alabama counties in the University of Alabama at Birmingham (UAB) Study of Aging.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
71
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(74 citation statements)
references
References 27 publications
(46 reference statements)
0
71
2
Order By: Relevance
“…22 Restricted life-space mobility is an important risk factor for the development of frailty, 18 cognitive decline, 3,4 and mortality. 6,7,18 Thus, an extended life-space mobility plays an important role in maintaining health and function in patients following TKA. In this study, the LSA score of 83.1 in the control group was lower than in communitydwelling older adults 22 ; however, the LSA score of 96.3 after the event in the intervention group exceeded the score of 91.8 of community-dwelling older adults in Japan.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Restricted life-space mobility is an important risk factor for the development of frailty, 18 cognitive decline, 3,4 and mortality. 6,7,18 Thus, an extended life-space mobility plays an important role in maintaining health and function in patients following TKA. In this study, the LSA score of 83.1 in the control group was lower than in communitydwelling older adults 22 ; however, the LSA score of 96.3 after the event in the intervention group exceeded the score of 91.8 of community-dwelling older adults in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…1 Restricted life-space mobility in older adults causes disability, 2 cognitive decline, 3,4 loss of independence, 5 and mortality. 6,7 A previous study reported that 61.1% of patients with knee and hip osteoarthritis (OA) have restricted life-space mobility as compared with 10.2% of people in the general population. 8 This restricted life-space mobility in patients with knee OA is associated with knee pain and restricted walking ability.…”
mentioning
confidence: 99%
“…The current study provides additional details about what components of mobility are impaired after hospitalization, specifically ability to walk a quarter mile, climb stairs, and drive, all of which have the potential to reduce community mobility. Unfortunately, loss of community mobility is also associated with nursing home placement and death, so it is an important marker of function for older adults …”
mentioning
confidence: 99%
“…Unfortunately, loss of community mobility is also associated with nursing home placement and death, so it is an important marker of function for older adults. 7,8 The study by Dharmarajan et al 5 also highlights the incomplete recovery from incident disability after hospitalization experienced by many older adults. While the majority of older adults recovered their ADL and IADL abilities, many did not recover.…”
mentioning
confidence: 99%
“…[2][3][4][5][6][7] Furthermore, reduced life-space mobility has been shown to predict greater mortality at 6 months and 2, 3, and 8 years. [8][9][10][11][12] Frequency of leaving ones house is a simple and easily quantifiable measure that may serve as a real-world surrogate for the more complex measurement of life-space mobility. Frequency of leaving the house was shown to predict subsequent functional status in frail, 13,14 and nonfrail community-dwelling people aged 70 to 78, 15 but a detailed analysis of frequency of leaving the house at different points over the aging trajectory has not been performed.…”
mentioning
confidence: 99%